Natural aggregates used for Light weight concrete – A Review. Issue 1 (December 2020) - Vijayan, D S; Arvindan, S.; Parthiban, D.; Saravanan, B.; Kalpana, M
Abstract: Lightweight concrete is comparatively lower weight than conventional concrete which helps to reduce the dead load in structure and act as an insulation against sound and heat however the strength of lightweight concrete is low compared with normal concrete, but it will be highly used for such requirement where the concrete is not expected to bear more loads. This paper provides more information about natural aggregates used for lightweight concrete furthermore it gives an insight of aggregates such as vermiculite, rice husk, volcanic cinder, saw dust, scoria, pumice and diatomite. This article also gives some of the research ideas for future approach in this area.